COMPARING THE EFFICACY AND SAFTEY OF PREGABALIN VS GABAPENTIN IN UREMIC PRURITUS IN PATIENTS OF CHRONIC KIDNEY INJURY UNDERGOING HEMODIALYSIS - Khan, Nudrat Jehngir; Wahaj,; Sara Haider,; Atifa Gilani,; Neelam Iqbal,; Syed Affan Ali,; Mohammad Arshad Abbasi, (Journal of Ayub Medical College Abbottabad, 2022)
Background: World has been facing an epidemic of non-communicable diseases including heart, metabolic and renal diseases. renal diseases have been commonly diagnosed and managed in low- and middle-income countries. Objective was to compare efficacy and safety of Pregabalin and Gabapentin in uremic pruritus among patients of chronic kidney injury undergoing haemodialysis. It was a comparative cross-sectional study, conducted at the Department of nephrology Abbottabad International Medical Institute. February 2021 to January 2022. Methods: Total of 90 cases were included in the study, which were diagnosed as chronic kidney disease stage 5 undergoing haemodialysis and presented with pruritus. Pruritus was gauged on numeric rating scale and patients score of more than 6 were included. Patients were randomly divided into two groups via lottery method. Group A received Pregabalin while group B received Gabapentin. Efficacy and safety were assessed in both groups at the end of six months. Results: Out of 90 dialysis dependent chronic kidney disease patients with significant pruritus included in the study, 61 (52.7%) patients were males and 29 (46.3%) were females. At the end of 6 weeks, we found out that 35 (38.9%) had no pruritus, 25 (27.8%) had mild, 19 (21.1%) had moderate while 11 (12.2%) had severe pruritus. After applying the chi-square test we found that Pregablin was statistically significantly more efficacious then Gabapentin (p-value-0.026). Sedation, nausea and blurred vision were found more in patients who took Pregabalin (p-value<0.001). Conclusion: Pregablin emerged out to be more efficacious with regards to reducing pruritus of the two medications compared in our study population while patients who took Gabapentin experience significantly a smaller number of side effects as compared to patients who were given Pregabalin.